2020
DOI: 10.1021/acs.est.0c05131
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transfer of Phthalate and Alternative Plasticizers from Indoor Source Products to Dust: Laboratory Measurements and Predictive Modeling

Abstract: Phthalate and alternative plasticizers are semivolatile organic compounds (SVOCs) and among the most abundant indoor pollutants. Although ingestion of dust is one of the major exposure pathways to them, migration knowledge from source products to indoor dust is still limited. Systematic chamber measurements were conducted to investigate the direct transfer of these SVOCs between source products and dust in contact with the source. Substantial direct source-to-dust transfer of SVOCs was observed for all tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 90 publications
2
32
0
1
Order By: Relevance
“…The drawback with phthalates is that once they are already in the indoor environment, their elimination becomes difficult. It must be taken into account that people that have spent a lot of time indoors, for several years [ 25 ], leading to health effects [ 26 , 27 ]. Phthalates have been detected in a variety of medical devices, such as intravenous tubing, umbilical artery catheters, blood bags and infusion tubing, enteral nutrition feeding bags, nasogastric tubes, among others.…”
Section: Phthalates Backgroundmentioning
confidence: 99%
“…The drawback with phthalates is that once they are already in the indoor environment, their elimination becomes difficult. It must be taken into account that people that have spent a lot of time indoors, for several years [ 25 ], leading to health effects [ 26 , 27 ]. Phthalates have been detected in a variety of medical devices, such as intravenous tubing, umbilical artery catheters, blood bags and infusion tubing, enteral nutrition feeding bags, nasogastric tubes, among others.…”
Section: Phthalates Backgroundmentioning
confidence: 99%
“…The kinetic partitioning of phthalates between settled dust and air was not considered. A considerable amount of SVOCs could transfer from the source to dust if the dust is directly settled on the surface of source materials, 61,62 which was also not considered at this stage. Parameters regarding particle dynamics, such as v d and P, were estimated based on the data reported for building environments.…”
Section: Limitations and Further Studymentioning
confidence: 99%
“…Indoor sources include building materials such as vinyl flooring, synthetic carpets and composite wood; consumer products such as electronics, personal care products, foam cushions, plastics, toys, scented cleaning agents and air fresheners [ 12 , 13 , 14 ]; and emissions from smoking, cooking and other combustion sources, including wood-burning, candles and flint lighters [ 2 , 15 , 16 , 17 ]. Studies have demonstrated direct transfer of chemicals from source product to dust; for example, Bi et al [ 18 ] found that the concentration of benzyl butyl phthalate (BBzP) in dust in direct contact with vinyl flooring was 10-fold higher than dust from non-vinyl surfaces in the same home.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies use concentration metrics (e.g., mg/kg) to measure contaminants in dust, but dust loading metrics (e.g., mg/m 2 ) are also important for exposure estimates [ 20 , 22 , 23 , 24 , 25 ]. Some studies that compared both metrics have reported a “dilution effect” caused by high dust loading, that is, dust concentrations of certain synthetic organics, such as phthalates and flame retardants, may decrease as dust loading increases [ 18 , 19 , 25 , 26 ]. Not all organics display an equivalent dilution effect, even under the same dust loading conditions [ 18 ], and Jílková et al [ 20 ] did not observe this relationship for any flame retardant that they studied.…”
Section: Introductionmentioning
confidence: 99%